Effect of different torques in cyclic fatigue resistance of K3 rotary instruments - Dirce Akemi Sacaguti Kawakami; George Táccio de Miranda Candeiro; Eduardo Akisue; Celso Luiz Caldeira; Giulio Gavini (Universidade Estadual de Campinas, 2015)
Aim: To assess the effect of different torque values on cyclic fatigue resistance of K3 rotary nickeltitanium (NiTi) files. Methods: Eighty K3 files, size 25 mm, taper 0.04 were divided in 4 groups according to different torques (0.5, 1, 2 and 6 Ncm) and were submitted to a cyclic fatigue test. This test was performed with a device that allowed the file to rotate inside a stainless steel artificial curved canal, simulating the pecking motion. Files rotated until fracture occurred and time to failure was recorded in seconds with a stopwatch. Data were analyzed by ANOVA and Tukey tests (p<0.05). Results: All groups were compared and only the group of 6 N.cm showed statistically significant difference (p=0.0002). Conclusions: For #25.04 K3 files, the evaluated torques up to 2 N.cm had no influence on cyclic fatigue resistance. Using 6 N.cm torque value resulted in lower resistance to cyclic fatigue.